PALLIATIVE PANCREATODUODENAL RESECTION IN PANCREATIC HEAD CANCER - T. G. Gevorkyan; I. A. Faynshteyn (Исследования и практика в медицине)
Purpose. Evaluation of the effectiveness of the method of palliative pancreatoduodenal resection for complications of advanced pancreatic head cancer.Patients  and methods. The article analyzes the results of treatment of 32 patients with advanced pancreatic head cancer in the Department of Radiosurgery of the FSBO «N. Blokhin National Medical Research Center of Oncology” of Ministry of Health of Russia. All patients underwent palliative pancreatoduodenal resection. In terms of the prevalence of the process, the patients were distributed as follows: 17 (53.1%) patients with the locally advanced process and 15 (46.9%) patients with distant metastases.Results. The average time of the operative intervention was 5.2 ± 0.3 hours, the average blood loss was 543.1 ± 1.3 ml, the average bed-day was 22.1 ± 0.6 days. In total, in the shortest postoperative period, complications were noted in 5 patients (15.6%). The total postoperative lethality after the PDR was 6.3%. In general, the results were divided into 4 groups: good results were recognized in 16.7% of cases, satisfactory enough — in 26.7%, less satisfactory, but a positive effect — in 50%, non-satisfactory results of treatment were found in 6.6% cases. Quality of life using the MOS-SF-36 questionnaire — if the average indicator on the scale of physical health was 41.2 ± 0.5 before the operation, then after a month of surgery it was significantly higher — 68.1 ± 0.9, according to the scale the average figure increased from 30.6 ± 0.9 to 71.5 ± 0.7. However, the differences between the values before and after surgery are statistically significant (p<0.01). The long-term survival rate for 1 year after the operation was 39.2%, 2 years after the surgery, 7.1%.Conclusions. Palliative pancreatoduodenal resection with a common pancreatic cancer in some cases can be an operation of choice that effectively eliminates the underlying pathological process and its complications in the form of mechanical jaundice, duodenal obstruction and pain syndrome and significantly improve the quality of life of patients.